Editorial and Mini-Review: Topical Oxygen Therapy for Diabetic Foot Ulcerations - Avenue Towards New Hope? (The Review of Diabetic Studies, 2019)
Diabetic foot complications now represent the 10th leading cause of disease burden and disability. Wound healing is impaired, leading to chronic ulceration. Local high oxygen concentration is required by the metabolically active cells in the wound, which may render the region hypoxic, even in the absence of peripheral arterial disease. Therefore, the contribution of hyperbaric oxygen to improved healing rates has been extensively investigated. More recent developments include products delivering topical oxygen therapy (TOT) directly at the wound site, either by continuous delivery or by pressurized systems. A very recent systematic review has found that TOT increases wound healing rates in chronic, less severe diabetic foot ulcers (DFUs), and it promotes high rates of healing in more severe ulcers. Thus, TOT appears to be very promising to improve healing in DFUs. We now need more experience regarding its therapeutic place in the algorithm of DFU management and in relation to optimal patient selection.